Therapeutic Efficacy and Safety of Dihydroartemisinin-Piperaquine (DP) for the Treatment of Uncomplicated Plasmodium Vivax Malaria: A Single Center Study - Salma Shaikh; Imran Ahmed; Sikander Munir Memon; Abdul Saleem; Hafeezullah Memon; Ayaz Babar (JLUMHS, 2017)
BACKGROUND: Ninety-five millions of Pakistan's 161 million people, roughly 60% of Pakistan’s population live in malaria endemic regions. Despite a well-established malaria control programme, 500,000 malaria infections and 50,000 malaria-attributable deaths occur each year in Pakistan. In Pakistan 15% population lives in high transmission area, 84% in low transmission and 1% in malaria free area, with 64% vivax and 36% Falciparum infections. OBJECTIVE: The objective of this study was to assess the therapeutic efficacy and safety of Dihydroartemisinin-piperaquine (DP) for the treatment of uncomplicated Plasmodium vivax malaria in subjects. METHODS: Its an observational study, conducted at Outpatient Department of Liaquat University Hospital Hyderabad, from December 2012 to December 2013. World Health Organization (WHO) standard protocol for efficacy studies (open-labelled clinical trial) was followed. The subjects with fever or history of fever for 48 hours aged between 6 months to 15 years with microscopically confirmed uncomplicated P. vivax infection were included. Total 109 patients fulfilled the inclusion criteria. Out of 109 patients, 103 had completed the study. Patients were treated with Dihydroartemisinin-piperaquine over three days. Clinical and parasitological parameters were monitored over a 42-days follow-up period to evaluate drug therapeutic efficacy. RESULTS: Adequate clinical and parasitological response of treatment (ACPR) for Dihydroartemisinin-piperaquine (DP) was seen in 102/103 (99.02%) patients, no early or late clinical failure was seen while late parasitological failure was seen on 21st day in one patient. No adverse events were reported. CONCLUSION: Dihydroartemisinin-piperaquine is safe and effective treatment option for uncomplicated vivax malaria.